2021
DOI: 10.1021/acs.est.1c00351
|View full text |Cite
|
Sign up to set email alerts
|

Emissions from Heated Terpenoids Present in Vaporizable Cannabis Concentrates

Abstract: Vaporizable cannabis concentrates (VCCs) consumed as a liquid (vaping) or a waxy solid (dabbing) are becoming increasingly popular. However, their associated emissions and impacts have not been fully described. Mixtures containing different proportions of twelve VCC terpenoids and high-MW compounds were heated at 100 -500 °C inside a room-sized chamber, to simulate emissions. Terpenoids, thermal degradation byproducts, and ultrafine particles (UFPs) were quantified in chamber air. Air samples contained over 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Within the C 4 –C 6 carbonyls shown in Figure , butyraldehyde, valeraldehyde, and hexanal appear to originate from the thermal degradation of cannabinoids and terpenes, which is consistent with Tang et al, while isobutyraldehyde, isovaleraldehyde, and 4-methylpentanal are from the thermal degradation of VEA (Scheme ). Although some products like formaldehyde can be produced from both VEA and THC oil, the production of formaldehyde from VEA appears more favorable since it involves a bond cleavage at a more substituted carbon (Scheme , path a), which forms a more stable alkyl radical intermediates than those from the unbranched aliphatic side chain of THC. , The same logic applies to the generation of 4-methylpentanal from VEA, which dominates the distribution of the isomer pair over hexanal.…”
Section: Results and Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Within the C 4 –C 6 carbonyls shown in Figure , butyraldehyde, valeraldehyde, and hexanal appear to originate from the thermal degradation of cannabinoids and terpenes, which is consistent with Tang et al, while isobutyraldehyde, isovaleraldehyde, and 4-methylpentanal are from the thermal degradation of VEA (Scheme ). Although some products like formaldehyde can be produced from both VEA and THC oil, the production of formaldehyde from VEA appears more favorable since it involves a bond cleavage at a more substituted carbon (Scheme , path a), which forms a more stable alkyl radical intermediates than those from the unbranched aliphatic side chain of THC. , The same logic applies to the generation of 4-methylpentanal from VEA, which dominates the distribution of the isomer pair over hexanal.…”
Section: Results and Discussionsupporting
confidence: 87%
“…Meehan-Atrash et al 30 identified degradation products from myrcene, limonene, and linalool, including methacrolein, hydroxyacetone, and methyl vinyl ketone. 78 Tang et al 57 found 11 thermal degradation products from a mixture of terpenoids, 7 of them are carbonyls including formaldehyde, acetaldehyde, acetone, acrolein, methacrolein, valeraldehyde, and hexanal. The methacrolein formed from vaped THC oil (Table 3) likely originates from terpene degradation, and its enhancement with VEA addition may be due to the aforementioned acceleration of volatilization or chemistry, as well as its source from VEA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for cancer risk from ENDS use may be important in relation to flavorants and humectants, which are present in the ENDS aerosols resulting from the heating and aerosolization of the e-liquid [ 29 ] . Furthermore, ENDS aerosol samples showed the presence of compounds such as arsenic, manganese, nickel, chrome, and lead [ 30 ] , while acrolein, methacrolein, tetrahydrocannabinol (THC), benzene, Vitamin E acetate, and terpenes were found in vaping cannabis mixtures [ 31 ] . Additionally, formaldehyde can be formed when the glycerol or propylene glycol in ENDS products are heated [ 32 ] ; it was also found in 4/16 e-liquids assessed by a 2022 study [ 33 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, newer versions of marijuana vaping come with a wide variety of chemicals, with both known and unknown cancer risks [ 41 ] . It is important to note that the experiment conducted by Tang et al may not be representative of the aerosol chemistry of cannabis vapor products by pregnant individuals or those in their households [ 31 ] . However, long-term use of nicotine and/or marijuana vaping needs to be addressed for cancer risk assessment and prevention based on available plausible biological pathways to cancer development.…”
Section: Introductionmentioning
confidence: 99%